Timing the arrival at 2340 m altitude for aerobic performance - Schuler, B.; Thomsen, J. J.; Gassmann, M.; Lundby, C. (Scandinavian Journal of Medicine & Science in Sports, 2006)
This study tested the hypothesis that maximal oxygen uptake (O2max) and performance increase upon altitude acclimatization at moderate altitude. Eight elite cyclists were studied at sea level, and after 1 (Day 1), 7 (Day 7), 14 (Day 14) and 21 (Day 21) days of exposure to 2340 m. Capillary blood samples were taken on these days before performing two consecutive maximal exercise trials. Acclimatization increased hemoglobin concentration and arterial oxygen content. On Day 1, O2max and time to exhaustion (at 80% of sea-level maximal power output) decreased by 12.8% (P<0.05) and 25.8% (P<0.05), respectively, compared with the corresponding sea-level values. Subsequently, these parameters increased by 3.2% (P<0.05) and 6.0% (P<0.05) from Days 1 to7, by 4.8% (P<0.05) and 5.7% (P<0.05) from Days 7 to 14, followed by 0.7% (P>0.05) and 1.4% (P>0.05) from Days 14 to 21, respectively. These data suggest that endurance athletes competing at altitudes around 2340 m should expose themselves to this altitude at least 14 days before competition.